Unexpected Musical Worlds of Vienna: Immigration and Music in Urban Centers - Hemetek, Ursula (Lidé města, 2012)
Vienna has been and still is the "City of Music" at a crossroads of international flow and immigration. This unique condition of Vienna arises from its history as the capital of the Austro-Hungarian monarchy, its later position as the eastern-most outpost of Western Europe during the Cold War, as the nearest shelter for refugees during the Balkan Wars, and, finally, as the center of working immigration from south-eastern Europe. For centuries, Vienna truly has been and today remains a multicultural city. This history and these conditions all lead to an astounding musical diversity. Drawing from several of my own recent research projects on the topic I try in my paper to deal with the production of music (active music making) by immigrants as well as with the "embeddedness" of these activities. I raise topics like the idea of the construction of ethnicity by performance, of the creation of "place" by music, of culturalization as well as deconstructing ethnic images. Collectivism as well as individuality are also important approaches. The methodological frame comes from studies in urban ethnomusicology as well as from recent discourses on diaspora and music. The music examples I use are part of Vienna's immigrant scene, especially from the communities from the former Yugoslavia as well as from Turkey. As ethnomusicology deals with music in social and political context, the socio-political background is an important focus of the paper.